Review of Japan's power generation scenarios in light of the Fukushima nuclear accident. (29th January 2014) - Zhang, Qi; Mclellan, Benjamin C.
SUMMARY Following on from the Fukushima Daiichi nuclear power plant accident, the Japanese government is now in the throes of reviewing its power policy. Under continuing policies of economic revival and greenhouse gas reduction, it is crucial to consider scenarios for the country to realize reliable, low‐carbon, and economic electricity systems in the future. On the other hand, the social acceptance of nuclear power will affect the final political decision significantly. Therefore, in the present study, proposed power generation scenarios in Japan in light of the Fukushima accident were reviewed comprehensively from economic, environmental, technological, resource, security, and social perspectives. The review concludes that in Japan, (i) renewable energy mainly solar and wind needs to be developed as fast as possible subject to various constraints, (ii) more gas power plants will be used to absorb the fluctuations of intermittent renewable energy and supply electricity gap, (iii) nuclear power will be reduced in the future, but a 0% nuclear power scenario by 2030 is unlikely to be a reasonable choice on most measures and (iv) the effective communication with the public is vital important. Copyright © 2014 John Wiley & Sons, Ltd.